Quality Costing and Supplier Social Sustainability as Antecedents of Supply Chain Performance: A Case of Rubber Industry of Indonesia - Kittisak Jermsittiparsert; Watcharin Joemsittiprasert; Wasino .; Cahyo Seftyono; Satya Budi Nugraha (International Journal of Supply Chain Management, 2019)
The prime objective of the current study is to investigate the relationship between supplier social responsibility, quality costing and supply chain performance of firms in the Indonesian rubber industry. The research focuses on the Indonesian rubber industry, which is attracting the foreign investors recently. This has resulted in the entrance of several manufacturers in the Indonesian markets. The author has employed the SEM-PLS to answer the research question raised in the current study. The researchers have suggested that the Indonesian rubber industry has started working on the sustainability issues across the supply chains. This has been supported with the results of this research. The researchers have suggested that the Indonesian rubber industry has started working on the sustainability issues across the supply chains. This has been supported with the results of this research. The research focuses on the Indonesian rubber industry, which is attracting the foreign investors recently. This has resulted in the entrance of several manufacturers in the Indonesian markets. The competition has become intention between the Indonesian rubber companies and the managers are focusing on the standards such as quality, cost, flexibility, and delivery for sustaining in the competition.